Assessment of the Risks Associated with the Handling and Transportation of Air Shipments Containing Lithium-Ion Batteries - Anna Kwasiborska; Sylwia Ścigaj (Energies)
Air transport, in addition to passenger transport, also transports air shipments containing hazardous materials. Hazardous materials include lithium-ion batteries, which can be carried both by passengers and by cargo aircraft. Due to the dynamic development of lithium-ion power supply technology, many devices are equipped with batteries that threaten air traffic safety. The article presents the results of research based on FAA reports of incidents involving lithium-ion batteries. The article aims to present a risk assessment for transporting lithium-ion batteries. Due to the emergence of new devices containing batteries, it is essential to analyze their transport to minimize threats and eliminate aviation incidents. The observations and the analysis of FAA reports showed possible threats from the transport of lithium-ion batteries on board aircraft. The matrix method used indicated the level of risk of transporting lithium-ion batteries. The risk assessment showed the need to monitor or implement corrective actions while transporting flight-ion batteries. Possible solutions were also presented to increase the safety level of transporting lithium-ion batteries.